Los teoremas de Cayley y de Lagrange para grupos difusos - Moya Padilla, Victor Hugo (2016)
A classic set A in a universe X can be characterized by its characteristic function_x000D_ A : X ! f0; 1g de ned by_x000D_ A(x) =8>><>>:_x000D_ 1; si x 2 A_x000D_ 0; si x =2 A;_x000D_ where 1 indicates membership and 0 non-membership of x to the set A._x000D_ A fuzzy set A can be characterized by its membership function A : X ! [0; 1],_x000D_ where the number A(x) 2 [0; 1] is called \grade of membership" of the element_x000D_ x to the set A; we note that the concept of fuzzy set generalizes the concept of_x000D_ classical set. The concept of fuzzy set was introduced by Zadeh [13] in 1965. After,_x000D_ Rosenfeld [9] en 1971 beginning the fuzzi cation of algebraic structures introducing_x000D_ the concept of fuzzy group and studying some of its properties. This marked the_x000D_ beginning of the study of fuzzy abstract algebra. Subsequently many researchers_x000D_ worked in this area [7]._x000D_ The main objective of this work is to demonstrate generalizations of Cayley theorems_x000D_ and Lagrange to fuzzy groups, that is to say, show fuzzy versions of classic_x000D_ Cayley theorems and Lagrange